The effect of reduced sprinkler programs on the main fungal pathogens of apple in environmentally sound production systems - Balla, Barbara; Fazekas, Mónika; Lakatos, Péter; Abonyi, Ferenc; Holb, Imre (Acta Agraria Debreceniensis, 2010)
Aim of our two-year study was to evaluate the possibilities of chemical use against key fungal pathogens (apple scab, apple powdery mildew and brown rot) in integrated and organic apple production. Therefore, first, disease incidence was compared in standard and reduced spray programmes and then each technological variation was evaluated from practical point of view. Altogether four spray programmes were compared. Standard and reduced spray programmes were performed in the integrated production. The same pesticides were used in the reduced spray programme compared to standard one but numbers of spray were reduced by 25% at the second half of the season. Standard and reduced spray programmes were also performed in the organic production and the numbers of spray were reduced by 40% in the reduced spray programme. Incidence of diseases was low in both standard and reduced spray programmes in integrated production. Diseases level was high in the organic production and disease increased significantly in the reduced spray programmes compared to standard programmes. Results showed that reduction in spray numbers at the second half of the season can be used practically in integrated production. Omission of sprays in organic production resulted in serious disease management risk; therefore, it is not recommended for practical use.